The Effect of Audiovisual and Booklet Education on Mothers' Behavior in Preventing Stunting - Renhoran, Farida; Purwati, Nyimas Heny; Anita, Anita (Indonesian Journal of Global Health Research, 2024)
Stunting describes a shorter or stunted body condition resulting from a lack of micro and macro nutrients over a long period of time. Stunting in children will have both short and long term impacts. Efforts that can be made to optimize maternal behavior in preventing stunting in children can be done through increasing parental knowledge, positive parental attitudes and good abilities in preventing stunting. This research aims to determine the effect of audio-visual and booklet-based education on mothers' behavior (knowledge, attitudes and psychomotor skills) in preventing stunting in children. This research is an experimental study with a control group. Data were analyzed using independent t-tests. The population in this study were mothers who had toddlers at the Debut Community Health Center, namely 123 people. By using the G*Power application, a sample size of 40 people was obtained. The research results showed differences in the average knowledge (p-value=0.000), attitude (p-value=0.000) and psychomotor (p-value=0.000) of mothers in the audio-visual education group with booklets. Providing audiovisual education has a greater influence on increasing mothers' knowledge, attitudes and psychomotor skills regarding stunting prevention at the Debut Community Health Center.